2019
DOI: 10.3892/ol.2019.10412
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the therapeutic accuracy of cone beam computed tomography‑guided nasopharyngeal carcinoma radiotherapy

Abstract: The aim of the present study was to determine the ability of cone beam computed tomography (CBCT) to improve the accuracy of nasopharyngeal carcinoma (NPC) radiotherapy by analyzing the setup and inter-fraction errors at different levels and directions of the target volumes. A total of 113 patients with NPC who were undergoing intensity-modulated radiotherapy were recruited for the present study. Each patient had at least three CBCT exams prior to the start of radiation therapy. Three anatomic bony landmarks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…However, IMRT still has some limitations such as its precise dose distribution of target region sketch has strict requirements. Moreover, several local and international studies have pointed out that in the process of radiation therapy, the weight loss in patients with NPC allows lymph nodes to disappear, and the initial tumor shrinkage factors may lead to a target area and endanger the organs (especially the spinal cord, brain stem, parotid gland), resulting in a change in anatomical position and actual exposure dose [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, IMRT still has some limitations such as its precise dose distribution of target region sketch has strict requirements. Moreover, several local and international studies have pointed out that in the process of radiation therapy, the weight loss in patients with NPC allows lymph nodes to disappear, and the initial tumor shrinkage factors may lead to a target area and endanger the organs (especially the spinal cord, brain stem, parotid gland), resulting in a change in anatomical position and actual exposure dose [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Daily image guidance may also enable customized margin for planning target volumes (PTV) and monitoring of geometric and dosimetric changes during the planned course of RT. [114][115][116][117][118] IMRT can be delivered using either sequential boost or simultaneous integrated boost technique. A phase III RCT 57 of 209 patients has shown similar efficacy and toxicities with these two approaches.…”
Section: Characteristics Of Studies Identified In the Literature Searchmentioning
confidence: 99%
“…The result showed that the mean couch displacement was small in both image-guided techniques and similar to other studies (Table 4). One study by Djordjevic et al [10] evaluated the set-up error in 80 HNC patients using daily OBI and reported that the mean couch displacement was -0.05 cm A-P, -0.06 cm S-I, and -0.06 cm L-R. Another study by Liu et al [19] evaluated the daily set-up error in 120 HNC patients (NPC) using CBCT and reported that the mean couch displacement in A-P, S-I, and L-R directions was 0.19 cm, 0.13 cm, and 0.15 cm, respectively. However, other studies have reported a more significant mean couch displacement with CBCT.…”
Section: Discussionmentioning
confidence: 99%